Validación fisiológica de un modelo de pie humano para estudio de patología de dedo en garra - González Torres, L. M.; Martínez Bocanegra, Marco A.; Vidal-Lesso, A. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The standing finite element models allow the study of their biomechanical-structural behavior. Research of this type provides podiatrists with knowledge in improving surgical techniques, thus allowing the exploration of new alternatives in the correction of biomechanical alterations in the lower extremities. Thus, reporting models in the literature with different types of contact in the joints, insertion of soft tissues such as the skin, as well as variation in the properties of the tissues. This research presents two numerical finite element models, healthy foot and claw toe pathology in the second radius. Based on the model of Mancera et al. (2020). The modifications include changes in load and contour conditions to simulate the "midstance" phase with 700 N load. The pathology model presents rotations and adjustments in the main soft tissues involved in the second radius of the foot. The two models were meshed and solved under the same conditions. The results of the simulation of the models are validated with the Costa Bartani and Kite angle. This was performed in the unloaded and loaded foot cases to verify that the model is within the parameters of the healthy foot. The Costa Bartani angle presented the greatest variation, while the Kite angle remained within the range value for a healthy foot. The models proposed during their evaluation show that pathologies that only involve the second radius of the foot affect the aforementioned angles, therefore, the biomechanical-structural behavior of the foot, allowing the study of other pathologies in future work.